La compétence comme dimension située et contingente, localement évaluée par les participants - Mondada, Lorenza (My University, 2006)
This paper aims a critical revision of the notion of "competence" within an interactionist perspective. It shows the way in which conversation analysis and ethnomethodology can inspire the approach of cognition and acquisition; it defines the "interactional competence" on the basis of forms of participation emerging from social interaction. This notion of participation is explored within a sequential and multimodal analysis of a videotaped corpus of interactions during a surgical operation. In the course of the operation, an audience composed by advanced trainees has the possibility of asking questions to the chief surgeon. The paper analyses the environments in which questions are inserted and the ways in which they are dealt with by the participants: they define the appropriate character and position of the question and locally evaluate the competence of the person who asks it.
Keywords: competence; interaction; participation; conversation analysis; sequentiality; questions